Early or late pregnancy loss and development of clinical cardiovascular disease risk factors: a prospective cohort study. (23rd September 2018) - Horn, J; Tanz, LJ; Stuart, JJ; Markovitz, AR; Skurnik, G; Rimm, EB; Missmer, SA; Rich‐Edwards, JW
Abstract : Objective: To assess the association between the outcome of a woman's first pregnancy and risk of clinical cardiovascular disease risk factors. Design: Prospective cohort study. Setting and population: Nurses' Health Study II. Methods: Multivariable‐adjusted Cox proportional hazards models were used to compute hazard ratios (HRs) and 95% confidence intervals (CIs) for the associations between first pregnancy outcome and hypertension, type 2 diabetes, and hypercholesterolemia. Main outcome measures: Hypertension, type 2 diabetes, and hypercholesterolemia. Results: Compared to women who reported a singleton live first birth, women with early spontaneous abortion (<12 weeks) had a greater rate of type 2 diabetes (HR: 1.20; 95% CI: 1.07–1.34) and hypercholesterolemia (HR: 1.06; 95% CI: 1.02–1.10), and a marginally increased rate of hypertension (HR: 1.05, 95% CI: 1.00–1.11). Late spontaneous abortion (12–19 weeks) was associated with an increased rate of type 2 diabetes (HR: 1.38; 95% CI: 1.14–1.65), hypercholesterolemia (HR: 1.11; 95% CI: 1.03–1.19), and hypertension (HR: 1.15; 95% CI: 1.05–1.25). The rates of type 2 diabetes (HR: 1.45; 95% CI: 1.13–1.87) and hypertension (HR: 1.15; 95% CI: 1.01–1.30) were higher in women who delivered stillbirth. In contrast, women whose first pregnancy ended in an induced abortion had lower rates of hypertension (HR: 0.87; 95% CI: 0.84–0.91) and type 2 diabetes (HR: 0.89; 95% CI: 0.79–0.99) than women with a singleton live birth. Conclusions: Several types of pregnancy loss were associated with an increased rate of hypertension, type 2 diabetes, and hypercholesterolemia, which may provide novel insight into the pathways through which pregnancy outcomes and CVD are linked. Tweetable abstract: Pregnancy loss is associated with later maternal risk of hypertension, type 2 diabetes, and hypercholesterolemia. Tweetable abstract: Pregnancy loss is associated with later maternal risk of hypertension, type 2 diabetes, and hypercholesterolemia.